PWE-039 The Interaction between The Hypoxia Inducible Factor-1Α (HIF-1Α) and ERBB Signalling Pathways in Colorectal Liver Metastases (CRLM). (17th August 2016) - Siriwardana, PN; Barrett, JE; Luong, T; Watkins, J; Singh, S; Kim, P; Hochhauser, D; Harris, A; Ng, T; Davidson, BR
Abstract : Introduction: Tumour hypoxia is associated with reduced survival by activating multiple molecular pathways such as, but not exclusively, HIF-1α and mTOR/AKT/PI3K pathways. It is also known to cause overexpression of Epidermal Growth Factor (EGFR)/HER1 in human cancer. HER2 (neu) signalling increases the rate of Hypoxia-Inducible Factor 1α (HIF-1α) synthesis. Overexpression of Erbb3/HER3 and Erbb4/HER4 is associated with a higher recurrence rate of stage 2 and 3 colorectal cancer. The aim of this study was to analyse the relationship between the expression of HIF-1α and members of the ErbB pathway in CRLM utilising a novel proteomic based collaborative Enzyme Enhanced Reactive (CEER) immunoassay. Methods: Protein lysates of from fresh frozen biopsies and formalin fixed paraffin sections of CRLM from 18 patients who had not undergone neoadjuvant chemotherapy prior to a potentially curative hepatectomy for CRLM were analysed. When multiple metastases were present biopsies and sections were obtained from the largest metastasis. CEER immunoassay was performed on the protein lysates to quantify the phosphorylated and non-phosphorylated forms of receptors; ErbB family receptors (HER1/EGFR, HER2/c-neu, HER3, HER4) and cMET, and phosphorylated downstream ErbB pathway factors AKT, PRAS, RSP6, ERK, and RSK, and CK. Immunostaining was performed on formalin-fixed-paraffin-embedded CRLM sections for HIF-1α. ErbB pathway factor quantification was segregated according to the HIF-1α expression status; HIF-1α +ve and HIF-1α -ve Results: HIF-1α was expressed in 15 (83%) of tumours. There was no significant difference between the expression of phosphorylated 'receptors', and phosphorylated forms AKT, PRAS, RSP6, ERK, MEK, and PI3K between the HIF-1α +ve and HIF-1α –ve groups. HER3 and IGF1R were higher; (median µm: range; 87 [74–344] vs 222 [60–404]) and (115 [85–206] vs 186 [90–285]) respectively in the HIF-1α +ve group, HER1, HER2, PI3K and CK levels were lower; (108 [40–316] vs 36 [22–46]), (698 [523–870] vs 481 [288–709]), (5338 [3334–6689] vs 2719 [1790–4193]), (5383 [1826–9799] vs 2719 [1789–4193]) respectively in the HIF-1α +ve group. Although a trend was observed, the difference did not reach statistical significance. Conclusion: HIF-1α may have a role in the overexpression of HER3 and IGF1R overexpression in CRLM. More research is needed to establish this interrelationship which would help in molecular based therapeutics for CRLM. Disclosure of Interest: None Declared